Teaching physics using virtual reality. - Savage, Craig; McGrath, Dominic; McIntyre, Tim; Wegener, Margaret (Australian Learning and Teaching Council, 2010)
Report of a project investigating university physics students' learning using computer simulations. The project focused on the teaching and learning of special relativity. The authors developed a simulation of a relativistic world called 'Real Time Relativity'. Around this they created a teaching package including a laboratory manual, background materials and evaluation instruments. Over 300 students in first year courses at The Australian National University and the University of Queensland used this package. Student learning was evaluated using a variety of methods including pre- and post-testing, exams, ethnographic observation and student interviews. Evaluation results were used to develop the simulation and the teaching package in an iterative cycle. [p.5, ed]